Determinan Kepatuhan Wajib Pajak Hotel dan Restoran dengan Trust kepada Pemerintah sebagai Variabel Mediasi - Negara, I Ketut Surya; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
This study aims to examine the effect of the determinants of hotel and restaurant taxpayer compliance with trust to the government as a mediating variable. The study population was 8,688 hotel and restaurant taxpayers registered with the Regional Revenue Agency/Pasedahan Agung, Badung Regency. Determination of the sample using a cluster random sampling technique with a total sample of 383 registered taxpayers from 2015 to 2020. The research data was obtained through distributing questionnaires and processed using the Smart PLS program. The results showed that the tax audit variables and tax sanctions had no effect on taxpayer compliance, while service quality and tax knowledge had a direct effect on taxpayer compliance. Trust to the government is able to mediate the effect of tax audits, tax sanctions and service quality on taxpayer compliance but is unable to mediate the effect of tax knowledge on taxpayer compliance. Keywords: Attribution Theory; Moral Theory; Tax Compliance; Trust to the Government.